O BNDES gera lucro econômico? Utilização da metodologia do EVA® para verificar a criação de valor ao acionista - Montone, Gina (2013)
The objective of this study was to determine whether the BNDES, in the period between 2000 and 2011 generated economic profit for its main shareholder, the Federal Government. We analyzed financial statements and notes published in this period to obtain data for the calculation of Economic Value Added or Economic Value added (EVA ®). This methodology deducts the cost of all capital employed in the company's from the operating profit after taxes. Furthermore, uses the weighted average cost of capital (WACC) as return on invested capital for calculating the cost of capital. The WACC weights the cost of debt, after deducting the rate of taxes on income and the cost of equity. The use of certain assumptions and developing some scenarios were required to estimate the cost of equity shareholder. Furthermore, some adjustments, such as the inclusion of dividends and interest on capital paid to shareholders by BNDES were performed for the calculation of EVA ®, and other accounting adjustments needed to estimate the cost of equity shareholder. At the end of the study, we observed that in all scenarios used to generate economic profit for used in all scenarios, the generation of economic profit was negative.